Menelusuri Akar Masalah: Faktor Penyebab Angka Kriminalitas Anak Di Bawah Umur - Fairuzzen , Mohamad Revaldy; Dr. Hj. Asmak Ul Hosnah, S.H, M.H.; Putra, Abil Arya (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The increasing phenomenon of criminal acts involving minors in Indonesia has become a crucial issue that threatens the future of the nation. This study aims to identify the types of crimes often committed by children, the causal factors, and the challenges in law enforcement for children. The research method used is quantitative, utilizing primary data from the Central Statistics Agency, the Indonesian Child Protection Commission (KPAI), and other related sources. The results of the study indicate that cases of crime by children are very diverse, including murder, sexual abuse, bullying, and drug abuse. Some of the main causal factors are inappropriate family parenting patterns, environmental and peer influences, and unsupervised access to media and technology. In addition, this study found challenges in the implementation of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), such as the lack of understanding of law enforcement officers about the concept of restorative justice and the lack of rehabilitation facilities in the regions. The results of this study emphasize the importance of the role of families, schools, and communities in preventing criminal acts by children and the need to optimize diversification and rehabilitation policies. This research is expected to be a reference for the government in formulating preventive and curative measures to reduce the number of child crimes and protect the future of the next generation. Keywords: Child Crime, Crime. Increase, Factors, Under Age Abstrak Fenomena meningkatnya tindak pidana yang melibatkan anak di bawah umur di Indonesia menjadi isu krusial yang mengancam masa depan bangsa. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis kejahatan yang sering dilakukan oleh anak, faktor-faktor penyebab, serta tantangan dalam penegakan hukum bagi anak. Metode penelitian yang digunakan adalah kuantitatif, dengan memanfaatkan data primer dari Badan Pusat Statistik, Komisi Perlindungan Anak Indonesia (KPAI), dan sumber terkait lainnya. Hasil penelitian menunjukkan bahwa kasus kejahatan oleh anak sangat beragam, meliputi pembunuhan, pelecehan seksual, bullying, dan penyalahgunaan narkotika. Beberapa faktor penyebab utama adalah pola asuh keluarga yang kurang tepat, pengaruh lingkungan dan teman sebaya, serta akses tanpa pengawasan terhadap media dan teknologi. Selain itu, penelitian ini menemukan tantangan dalam penerapan Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak (UU SPPA), seperti kurangnya pemahaman aparat hukum tentang konsep restorative justice dan minimnya fasilitas rehabilitasi di daerah. Hasil studi ini menekankan pentingnya peran keluarga, sekolah, dan masyarakat dalam pencegahan tindak pidana oleh anak serta perlunya optimalisasi kebijakan diversifikasi dan rehabilitasi. Penelitian ini diharapkan dapat menjadi acuan bagi pemerintah dalam merumuskan langkah-langkah preventif dan kuratif guna menekan angka kriminalitas anak dan melindungi masa depan generasi penerus. Kata Kunci: Pidana Anak, Kejahatan. Peningkatan, faktor, dibawah umur